IMPLEMENTATION OF AN INTEGRATED PBL MODEL IN SOCIAL EMOTIONAL LEARNING IN INDONESIAN LANGUAGE LEARNING IN CLASS IV PRIMARY SCHOOL - Yulianto, Feri; Mushafanah, Qoriati (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
This research discusses the implementation of the Problem Based Learning (PBL) learning model which is integrated with Social Emotional Learning (SEL) in Indonesian language learning in class IV elementary school. Aims to introduce students to learning that is oriented to daily life problems in the surrounding environment. Apart from that, to develop students' social emotional skills, related to empathetic attitudes through learning Indonesian with persuasive sentence material in class IV elementary school. The method used in this research is descriptive qualitative. This research was conducted in class IV at SDN Sambirejo 02 Semarang. The research results show that the implementation of the SEL integrated PBL model in Indonesian language learning in grade IV elementary school brings positive results. The use of this PBL model focuses on real problems faced by students, in this case related to bullying behavior. Apart from that, through this learning, students can develop learning attitudes such as empathy, discipline, responsibility and honesty. The results of the analysis show that students' learning attitudes have a correlation with students' cognitive achievement scores in the range of 0.55 - 0.78 (fairly strong - strong) and a classical completeness level of 82.75% in learning Indonesian with persuasive sentence material in class. IV.